Hidden technicians; music and radio-making at 3-PBS in the Prince of Wales. (August 2020) - Tebbutt, John
This article explores the role played by radio broadcast technicians in the early period of the volunteer-run community radio station PBS-FM, in Melbourne. It covers the tenure of the broadcaster at the Prince of Wales (PoW) hotel in the city bayside suburb of St Kilda between 1980 and 1984. The article aims to assess the link between radio and music in the light of the problematic relationship these elements have had historically in popular music studies. The article specifically addresses the role of volunteer technicians in facilitating live music broadcasts at PBS, which became a signature format for PBS and helped establish it as an important community station in the new sector as well as a component of Melbourne's emerging role in Australian and international music.